A Mixed Method Study on Supportive Supervision of Community Health Workers From Central India - G Revadi; Ankur Joshi; Abhijit P. Pakhare (Indian Journal of Community Medicine)
Background: Supportive supervision of the Community health workers (CHWs) is critical for their efficient functioning in various health programmes. CHWs in India are supervised by facilitators known as ASHA Sahyogini. Our study aimed to investigate the linkage between the knowledge and skills of CHW facilitators and their CHWs. To understand the problems encountered by the CHW facilitators while assisting their CHWs. Also, to determine the perceptions of CHWs on the nature of supportive supervision of their facilitators. Materials and Methods: A mixed-method explanatory study using purposive sampling was conducted in a rural block of Madhya Pradesh (Central India). The CHWs were categorized into relatively high performing (RHP) and relatively low performing (RLP) groups based on their performance-based incentives received during (2017-2018). The quantitative component comprised of self-administered questionnaire and skill assessment while the qualitative component comprised of three focused group discussions with RHP, RLP CHWs and their facilitators. Results: The mean (SD) supportive supervision score given by CHW facilitators were found to be significantly associated with CHW’s performance. Problems faced by CHW facilitators while assisting their CHWs resulted from inadequate education of CHWs, insufficient incentives, transport problems and repetitive surveys. While some CHWs perceived to have received good assistance from their facilitators, there were a few who were not dependent on their facilitators and executed duties by themselves. Conclusion: CHW’s performance cannot be ascribed completely to the CHW facilitator’s performance. The challenges perceived by CHW facilitators were unmodifiable and required them to strongly motivate and support their CHWs to improve their functionality.